2013
DOI: 10.1155/2013/304894
|View full text |Cite
|
Sign up to set email alerts
|

Colon Mucosa Exhibits Loss of Ectopic MUC5AC Expression in Patients with Ulcerative Colitis Treated with Oral Tacrolimus

Abstract: Background. Tacrolimus (FK506) is effective for patients with ulcerative colitis (UC). However, there are few reports on tacrolimus therapy (TT) with respect to the relationship with endoscopic and clinicopathologic findings. Methods. Thirty patients with moderate/severe active UC refractory to or dependent on corticosteroid were treated with oral tacrolimus. The expression of ectopic MUC5AC in the colon was pathologically analyzed before and at 12 weeks after TT, evaluating the Mayo score and steroid-sparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…We can obtain more evidence, almost all from retrospective studies, demonstrating relatively good efficacy rates in UC and CD. In UC, retrospective studies have reported remission rates between 9.3-80%, which reflects the high variability between the study population, route of administration, mean drug blood levels and the criteria for evaluating response (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Remission rates demonstrated a similar variability ranging from 9.4-75% in clinical trials and prospective studies (1,2,(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We can obtain more evidence, almost all from retrospective studies, demonstrating relatively good efficacy rates in UC and CD. In UC, retrospective studies have reported remission rates between 9.3-80%, which reflects the high variability between the study population, route of administration, mean drug blood levels and the criteria for evaluating response (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Remission rates demonstrated a similar variability ranging from 9.4-75% in clinical trials and prospective studies (1,2,(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 96%
“…The drug was maintained for a median duration of 11 months (IQR [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Ten patients received the drug for at least 12 months.…”
Section: Treatment Characteristicsmentioning
confidence: 99%
“…MUC1 is up-regulated and poorly glycosylated in colonic tissue from children with inflammatory bowel disease [10]. Several studies have also reported that MUC5AC plays an important role in inflammatory bowel disease [8, 11]. …”
Section: Discussionmentioning
confidence: 99%
“…Disease activity before and after anti-TNF-α therapy was measured using the Mayo score [also known as the disease activity index (DAI)] and the EAI. [ 10 , 11 ] Patients were included who had a DAI ≥ 6 points and an EAI ≥ 2 points before the start of anti-TNF therapy. The exclusion criteria were as follows: age less than 20 years, severe infection, severe heart and renal disorders, pregnant or nursing, malignancy, and previous colectomy.…”
Section: Methodsmentioning
confidence: 99%
“…Cytomegalovirus infection was ruled out by pathological analysis of lesions. [ 11 ] After reading a brief description of IFX and ADA, all of the eligible participants were provided a questionnaire to determine their treatment preference after informed consent was obtained. [ 1 ] According to the protocol, IFX was administered at 5 mg/kg to patients with active UC at weeks 0, 2, and 6, and intravenous IFX injections of 5 mg/kg were administered as maintenance doses every 8 weeks thereafter.…”
Section: Methodsmentioning
confidence: 99%